Impact of Cover, Copy, and Compare on fluency outcomes for students with disabilities and math deficits: A review of the literature. Issue 1 (2nd January 2017) - Stocker, James D.; Kubina, Richard M.
ABSTRACT: Fluency, a combination of response accuracy and speed, enables students to work efficiently through academic tasks. Students with disabilities and math deficits often struggle to learn math facts fluently. Although issues with fluency frequently coexist with a disability, problems gaining fluency also stem from a lack of practice and appropriate rehearsal activities routinely included in curricula. Absence of math fact fluency leads to future problems with higher level math curricula and tasks necessary for successful living and employment. Cover, Copy, and Compare (CCC), a self-managed intervention, has demonstrated promise toward increasing math facts fluency. The present literature review examines the implementation of CCC as a fluency intervention for students who have disabilities or who demonstrate skill deficits in math facts and its subsequent impact on such students' fluency outcomes. Results from the literature review indicate CCC increased fluency levels for all of the participants. The evidence suggests CCC interventions may help students acquire and practice diverse math content.